MANAJEMEN STRATEGI PEMASARAN PENDIDIKAN DALAM MENINGKATKAN KUANTITAS PESERTA DIDIK BARU DI MI AL MUSTHOFA KARIM TASIKMALAYA - Pauji, Ade Ikbal; Badruzaman, Muhammad Hilmi Surya (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2025)
Competition among educational institutions requires madrasahs to implement marketing strategies that strengthen institutional image and attract new students. This study aims to analyze the implementation of educational marketing management strategies at MI Al Musthofa Karim Tasikmalaya and their relation to the increase in student enrollment. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation, while data validity was ensured through triangulation of sources and techniques. The findings indicate that marketing strategies are executed through managerial functions consisting of planning, organizing, implementation, and monitoring–evaluation. Strategy implementation combines offline promotion—such as brochure distribution, school visits, religious activities, and door-to-door outreach—with online promotion via social media. Operationally, the strategies are reflected in the application of the Marketing Mix 7P, including integrated educational programs, affordable fees, varied promotional media, strategic location, competent human resources, transparent service processes, and visible physical evidence of institutional achievements. Supporting factors include teacher competence, community networks, distinctive programs, and accessibility, while inhibiting factors involve limited facilities, competition from public schools, technological constraints, and suboptimal coordination during school holidays. The results affirm that effective madrasah marketing depends not only on promotional activities but also on the alignment between service quality and communication strategies. Therefore, adaptive and well-managed marketing strategies contribute to strengthening institutional image and increasing new student enrollment at the Madrasah Ibtidaiyah level.